Hubungan Karakteristik Sosial Ekonomi dengan Partisipasi Wanita Tani dalam Program Pekarangan Pangan Lestari - Kirana, Bunga; Sugihardjo, Sugihardjo; Widiyanti , Emi (Jurnal Sosial Ekonomi Pertanian, 2024)
Fulfillment of nutritious and sufficient food is the human right of every Indonesian people to create quality human resources. One of the programs and activities that have been implemented to support the food security program is the sustainable food program. The success of this program is participation that is related to the socio-economic characteristics of the farmers themselves. This research aims to (1) determine the socio-economic characteristics of women farmers in Gemawang District (2) examine the participation of women farmers in the sustainable food program in Gemawang District (3) analyze the relationship between socio-economic characteristics and the level of participation of women farmers in the sustainable food program in Gemawang District. The basic method used in this research is quantitative research, using research instruments such as questionnaires. The population was 37 people with census sampling. Data analysis used the spearman rank test using the IBM SPSS 25 application. The study showed a significant relationship between the socio-economic characteristics of non-formal education, farming experience and perceptions of the goals and benefits of women farming participation in the sustainable food program in Gemawang District, Temanggung Regency.